Effects of Invariant NKT Cells on Parasite Infections and Hygiene Hypothesis - Jun-Qi Yang; Yonghua Zhou; Ram Raj Singh (Journal of Immunology Research)
Invariant natural killer T (iNKT) cells are unique subset of innate-like T cells recognizing glycolipids. iNKT cells can rapidly produce copious amounts of cytokines upon antigen stimulation and exert potent immunomodulatory activities for a wide variety of immune responses and diseases. We have revealed the regulatory effect of iNKT cells on autoimmunity with a serial of publications. On the other hand, the role of iNKT cells in parasitic infections, especially in recently attractive topic “hygiene hypothesis,” has not been clearly defined yet. Bacterial and parasitic cell wall is a cellular structure highly enriched in a variety of glycolipids and lipoproteins, some of which may serve as natural ligands of iNKT cells. In this review, we mainly summarized the recent findings on the roles and underlying mechanisms of iNKT cells in parasite infections and their cross-talk with Th1, Th2, Th17, Treg, and innate lymphoid cells. In most cases, iNKT cells exert regulatory or direct cytotoxic roles to protect hosts against parasite infections. We put particular emphasis as well on the identification of the natural ligands from parasites and the involvement of iNKT cells in the hygiene hypothesis.